'Providing simulation experiences for large cohorts of 1st year nursing students: Evaluating quality and impact' - Rochester, S.; Kelly, Michelle; Disler, R.; White, H.; Forber, J.; Matiuk, S. (Elsevier BV, 2012)
To provide each student within a large cohort the opportunity to participate in a small group simulation that meets recognised quality indicators is a challenge for Bachelor of Nursing programmes in Australia. This paper, as part of a larger longitudinal study, describes one approach used to manage a simulation for 375 1st year nursing students and to report on the quality of the experience from the student's perspective. To ensure quality was maintained within the large cohort, aspects of the simulation were assessed against the following indicators: alignment with curriculum pedagogy and goals; preparation of students and staff; fidelity; and debriefing. Data obtained from a student focus group were analysed in the context of the quality indicators. The following themes emerged from the data: knowing what to expect; assuming roles for the simulation; authenticity and thinking on your feet; feeling the RN role; and, preparation for clinical practice. This paper demonstrates it is possible to provide students in large cohorts with active participatory roles in simulations whilst maintaining quality indicators.